Identification of Shared and Asian‐Specific Loci for Systemic Lupus Erythematosus and Evidence for Roles of Type III Interferon Signaling and Lysosomal Function in the Disease: A Multi‐Ancestral Genome‐Wide Association Study. Issue 5 (29th March 2022) - Wang, Yong‐Fei; Wei, Wei; Tangtanatakul, Pattarin; Zheng, Lichuan; Lei, Yao; Lin, Zhiming; Qian, Chengmin; Qin, Xiao; Hou, Fei; Zhang, Xinyu; Shao, Li; Satproedprai, Nusara; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a prototypical autoimmune disease with differences in prevalence and severity among ancestral groups. This study was undertaken to identify novel genetic components, either shared by or distinct between Asian and European populations. Methods: Both trans‐ancestral and ancestry‐specific meta‐analyses of genome‐wide association studies (GWAS) for SLE were performed, involving 30, 604 participants of European, Chinese, or Thai origin. Using public epigenomic data and expression quantitative trait loci, fine‐mapping analyses were conducted to identify putative causal variants and genes for the newly identified loci. Performance of polygenic risk scores for the Thai cohort was evaluated by comparing different training data. Results: A 1‐bp deletion upstream of IFNLR1 was found to be associated with SLE, with the risk allele correlated with increased expression of IFNLR1 . This gene encodes interferon‐λ (IFNλ) receptor 1, providing evidence of a role of type III IFN signaling in SLE. An intronic variant in SLC29A3 was found to be associated with SLE in Asians only. The putative risk variant may modulate SLC29A3 expression in a monocyte‐specific manner. SLC29A3 encodes a lysosomal nucleoside transporter, and subsequent analyses suggested that reduced lysosomal function and phagocytosis might be the mechanism underlying this association. Ancestry‐shared loci in or near TAOK3, CHD9, CAMK1D, ATXN1, and TARBP1 and Asian‐specific loci close to PEX2, FCHSD2, and TMEM116 also reached the genome‐wide significant association with SLE. In addition, trans‐ancestral meta‐analysis was shown to be valuable in risk prediction for individuals without ancestry‐matched data. Conclusion: In this study both shared and Asian‐specific loci for SLE were identified, and functional annotation provided evidence of the involvement of increased type III IFN signaling and reduced lysosomal function in SLE.